Modelowanie indeksu cen nieruchomości mieszkaniowych w Polsce - Rafał Zbyrowski (Studia i Materiały)
The main purpose of this article is to describe a dependence between prices of flats and index of creditworthiness in Poland. In the empirical part of this paper, the author tests mentioned relations according to Engle-Granger’s procedure. Moreover, the long time relation was verified by Johansen’s procedure and a VAR model. This case leads to the examination and estimation cointegration with testing lags between very important variables on the real estate market in Poland. The database used in the research contains monthly observations from the middle of 2010 to the begining of 2014.